Keeping on Country: Understanding and Responding to Crime and Recidivism in Remote Indigenous Communities. (August 2017) - Dawes, Glenn; Davidson, Andrea; Walden, Edward; Isaacs, Sarah
Abstract : Objectives: The objectives of this qualitative study were to examine local perspectives on the causes of crime and recidivism in two remote Indigenous communities, and provide a series of recommendations regarding more effective responses that could be implemented by way of justice reinvestment. Method: This study was coordinated by a multi‐disciplinary research team that actively engaged the community in every stage of the research process, through a culturally and ecologically informed participatory action research design. Data was gathered through semi‐structured individual and focus group interviews with three cohorts: (a) offenders who had been incarcerated on at least one occasion ( n = 20); (b) offenders' families ( n = 20); and, (c) service providers working with offenders ( n = 20). Data was also gathered through over 40 informal conversations. Data collection occurred over a period of 18 months, with participants recruited by Indigenous researchers and community members. Data Analysis: Interviews were transcribed and analysed by NVivo qualitative data processing software in the first instance. The core research team and community members reviewed this analysis in order to collectively identify major themes and patterns in the perspectives of participants. Conclusion: People in remote Indigenous communities are aware of the complex issues associated with crime in their community and have clear ideas regarding what can be done. We argue that in order to understand and address Indigenous crime and over‐representation in the criminal justice system, the perspective of Indigenous people must be elevated and communities empowered to identify and implement ecologically and culturally informed solutions that will work for them.